(untitled) (Journal of history-rus, 2023)
Annotation At the beginning of the 20th century, the life, socio-political, and educational activities of Akhmet Zhantalin, who lived in a controversial period in society, are still among the few research works that have been scientifically analyzed from a more complete and systematic point of view. During the Soviet era, the prerequisites for a special study of this issue were not created. Only after the independence of the country did the deeds of our historical figures who fought for the independence of their people begin to enter the history of our motherland. On this basis, this article attempts to study Akhmet Zhantalin’s socio-political and educational-scientific activities in a new historical way in accordance with the requirements of today. Akhmet Zhantalin, who was a jadidist, and one of the founders of the new period in the development of public thoughts, who inspired the national, political and legal awakening of the Kazakh people. The study of socio-political educational activities and the scientific heritage of A. Zhantalin from the perspective of historical reality. A. Zhantalin’s approach to socio-political and cultural, educational issues was researched, analyzed, reported and A. Zhantalin’s educational activity was analyzed. Great attention was paid to Zhantalin’s multifaceted social and educational work and views. In this article, we consider A. Zhantalin’s sociopolitical and other multidisciplinary activities and views for the first time. His contribution to the creation of the ideology of the national liberation struggle was shown in the newspaper «Qazaq» through the first nationwide political publication. Simultaneously, his social and educational activities were considered in detail for the first time. His teaching activities in the field of education in order to eliminate mass illiteracy, the opening of schools, his work in the development of Kazakh culture, his place in the fate of the Kazakh nation, and his advanced ideas on the land were taken for scientific analysis based on new documentary data and memoirs. Keywords: A. Zhantalin, Alash, jaditanism, educational activities, scientific heritage.